Hubungan Regulasi Emosi dan Perilaku Cyberbullying pada Mahasiswa Dewasa Awal Pengguna Intstagram dan TikTok di Kota Jambi - Gabriel Alexandro; Jelpa Periantalo; Marlita Andhika Rahman (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
The development of digital technology and the widespread use of social media, particularly Instagram and TikTok, have opened opportunities for online interaction but also increased the risk of cyberbullying. Cyberbullying is aggressive behavior via digital media intended to harm or degrade others. One psychological factor believed to influence this behavior is emotional regulation, which is the ability to manage and express emotions appropriately in different situations. This study aims to examine the relationship between emotional regulation and cyberbullying behavior among early adult students in Jambi. A quantitative approach with a correlational design was used, involving 127 students aged 18–25 years, selected through purposive sampling. Data were collected using an online questionnaire, which included an emotional regulation scale and a cyberbullying behavior scale. Data analysis was conducted using the Pearson Product Moment correlation test with SPSS software. The results showed a significant negative relationship between emotional regulation and cyberbullying behavior, with a correlation coefficient of r = -0.632 and a significance level of p < 0.001. This indicates that students with better emotional regulation skills are less likely to engage in cyberbullying. Thus, enhancing emotional regulation skills could be an effective strategy in preventing cyberbullying among students.